2023
DOI: 10.1017/jns.2023.61
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic effects of papaya (Carica papayaL.) juice on rats fed on a high fat and fructose diet

Abstract: Papaya (Carica papaya L.) is a highly nutritious and less-caloric fruit, commonly consumed for its minerals and vitamins and hence may help in controlling obesity and abdominal discomforts. The present study investigated the hypolipidaemic effects of papaya juice extract on male Albino Wistar rats (7 weeks old; 185 ± 17 g) fed on a high fat and fructose diet (HFFD) for 6 weeks. The rats were divided into groups I–IV of five rats each and fed on either a HFFD (i.e. the Control), HFFD + 200 mg papaya, HFFD + 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…2 G). The anti-obesity and hypolipidemic properties of PL juice supplementation in our study are consistent with those observed in other studies on animal models [ 30 ]. Papaya contains many phytochemicals that act as antioxidants and anti-inflammatory agents, including phenolic compounds, benzyl isothiocyanate, and tocopherol [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2 G). The anti-obesity and hypolipidemic properties of PL juice supplementation in our study are consistent with those observed in other studies on animal models [ 30 ]. Papaya contains many phytochemicals that act as antioxidants and anti-inflammatory agents, including phenolic compounds, benzyl isothiocyanate, and tocopherol [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…IR and GLUT4 muscle expression was elevated by ethanolic PL extracts in diabetic mice, as demonstrated by Roy et al [ 37 ]. This effect may be due to papaya's phenols and flavonoids [ 30 ]. Phytochemicals such as gallotannins, 3-taraxerol, Astragalus polysaccharide, Berberine, and vanillic acid contribute to insulin signaling by increasing GLUT4 translocation, adiponectin secretion, PKB-Ser473 phosphorylation, decreased activity of glucokinase (GK), increased activity of glucose-6-phosphatase (G6Pase), and beta-cell stimulation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The active compound contained in A. catechu will inhibit the gamma amino benzoic acid reaction, which can cause paralysis of worms [32], besides that A. catechu has pharmacological therapeutic effects have various benefits, including can be used for the treatment of diseases caused by parasites and also several other diseases [14].…”
Section: Discussionmentioning
confidence: 99%